PEDAGOGICAL FACTORS FOR INCREASING THE EFFECTIVENESS OF INNOVATIVE TECHNOLOGIES IN TEACHING THE RUSSIAN LANGUAGE IN PEDAGOGICAL EDUCATION - Isroilova Sanobarkhon Mamedjanovna (Scholars Digest Publishing, 2025)
This article covers the issues of effective use of innovative technologies in teaching the Russian language in the pedagogical education system. It analyzes the professional competence, methodological training and digital literacy of the teacher as the main factors determining the success of innovative processes. There have also been studies of ways to improve the quality and motivation of students ' knowledge through the integration of interactive techniques into the learning process, the use of digital educational resources and the development of communicative competence.
Keywords: Pedagogical education, innovative technologies, Russian language education, teacher competence, digital literacy, interactive methods, communicative competence, educational effectiveness.